Electronic health intervention to manage symptoms of immunotherapy in patients with cancer (SOFIA): Results from a randomized controlled pilot trial - Sauer, Christina; Zschäbitz, Stefanie; Krauß, Jürgen; Walle, Thomas; Haag, Georg Martin; Jäger, Dirk; Hiller, Kiriaki; Bugaj, Till Johannes; Friederich, Hans-Christoph; Maatouk, Imad (Cancer, 2024)
Background For patients receiving immune checkpoint inhibitors, early detection of immune-related adverse events (irAEs) is critical for one’s safety. To this end, a smartphone app (SOFIA) was developed that featured the assessment of electronic patient-reported outcomes (ePROs) focusing on irAEs as well as a set of comprehensive supportive information. Its feasibility and preliminary efficacy were evaluated in a randomized controlled trial (RCT). Methods Patients who received immune checkpoint inhibition therapy were randomly assigned to an intervention group (IG) or a control group (CG; care as usual). During the 12-week intervention period, IG patients used SOFIA to report twice weekly ePROs and receive cancer- and immunotherapy-relevant contents. Before a patient’s next clinical visit, the physician in charge was given the ePRO reports. The primary objective was to test the feasibility of SOFIA. Furthermore, the preliminary efficacy of SOFIA for health-related quality of life (HRQOL), psychosocial outcomes, and medical data was examined. Clinical outcomes were assessed at baseline (T0), post-intervention (T1), and a 3-month follow-up (T2). Results Seventy-one patients were randomized to the IG (n = 34) or the CG (n = 37). SOFIA showed high feasibility and acceptance. At T1, patients in the IG reported significantly better HRQOL and role functioning and less depression, distress, and appetite loss. No significant differences were revealed regarding medical data, the utilization of supportive care services, or survival. Conclusions SOFIA showed high feasibility and acceptance and improved HRQOL and psychosocial outcomes. These results suggest further evaluation of efficacy in a large-scale confirmatory multicenter RCT.